A study on advertising awareness on online gaming addiction among children / Nor Iffah Mohamad Rizal - Mohamad Rizal, Nor Iffah (2018)
Children are usually exposed to the online gaming through the internet. Overuse of internet or social networking can make children become an addicted to online game. Online gaming among children especially in school holiday is one of the causes for their failed mastering socialize skill and communicate. National University of Malaysia Psychology Lecturer, Prof. Dr. Khaid- zir Ismail said, this happen because their lack of exposure and interaction with the community. By this research its aims to investigating the causes why children involve playing online game and to create awareness for young parent to control the use of gadgets in children. The method of this study by using a quantitative research which can help to get a deeper and better understanding of online game addiction. The finding is based on observation, collecting data on questionnaire and previous research and books. Hopping this research will give benefit to the organization involved so that this issue can be reduce or solve.